SOSIALISASI KEBUTUHAN DAN KETERSEDIAAN AIR IRIGASI PADA DESA SEUNEBOK ACEH, KECAMATAN BENDAHARA, KABUPATEN ACEH TAMIANG - Hanifah Hanni, Puteri; Zakia, Siti; Sihotang, Efrinton; Qausar, Riyal; Mutia, Eka; Fajri, Haikal (Fakultas Teknik, Universitas Samudra, 2024)
The need for water by all living creatures is a need that cannot be separated from every day of life. In the use of water, especially for rice fields, in order to meet food needs and regional development, the Indonesian Government is carrying out development efforts in the irrigation sector which aims to make it directly felt by the community in meeting water needs. Therefore, it is necessary to analyze the availability and need for irrigation water in the Seunebok Aceh village with the Seunebok Bacee irrigation area which is a rice field with a planting pattern of only rice. The research method is direct observation in the field. The results of the evaluation of the availability and need for irrigation water in this study show that the availability of water in Seunebok Village, Aceh, is 134.56 m3/s, which is very sufficient to support the irrigation water needs in the rice fields in the village, namely with an NFR of 6.06 mm/day and the need for irrigation water. water (DR) of 1.08 l/sec/ha. And the planned flood discharge at the smallest return period (Q2) was 20,153 m3/s and at the largest return period (Q50) was 31,952 m3/s and the main discharge using the F.J Mock Method was 12,078 m3/s.